Identification of Hypoxia-Related Molecular Classification and Associated Gene Signature in Oral Squamous Cell Carcinoma - Li, Chen; Chen, Xin; Ren, Xiaolin; Chen, Jia-lin; Chen, Hao; Yu, Jing-jia; Ran, Qiu-chi; Kang, Shuang; Chen, Xi-meng; Zhao, Zhen-jin (Frontiers in Oncology, 2021)
High heterogeneity of oral squamous cell carcinoma (OSCC) is the main obstacle for individualized treatment. Recognizing the characteristics of different subtypes and investigating the promising strategies for each subclass are of great significance in precise treatment. In this study, we systematically evaluated hypoxia-mediated patterns together with immune characteristics of 309 OSCC patients in TCGA training set and 97 patients in GSE41613 testing set. We further identified two different hypoxia subtypes with distinct immune microenvironment traits and provided treatment programs for the two subclasses. In order to assess hypoxia level individually, we finally constructed a hypoxia related risk score, which could predict the clinical outcome and immunotherapy response of OSCC patients. In summary, the recognition of different hypoxia patterns and establishment of hypoxia related risk score might enhance our understanding of the tumor microenvironment of OSCC and provide more personalized treatment strategies in the future.